Control of an Ultrafast Electric Vehicle Charger Based on a Series-Parallel Modular Multilevel Converter - Diaz-Diaz, M; Vidal-Nunez, C; Rajendran, S (Institute of Electrical and Electronics Engineers Inc., 2022)
There is an ongoing trend of upscaling the nominal power of electric vehicle chargers to reduce the charging time of modern electric vehicles. As a result, ultra-fast electric vehicle chargers have reached megawatt power ratios for large EVs such as trucks and heavyweight vehicles. Therefore, Modular Multilevel Converters are acquiring popularity in EV charging applications. In this context, this paper proposes a novel EV charger based on a Series-Parallel Modular Multilevel Converter. In this proposal, the proposed converter is regulated to perform medium-voltage low-frequency alternating current conversion to low-voltage medium-frequency alternating current required for ultra-fast charging of electric vehicles. In addition, simulation results obtained with a 500 kW SeriesParallel Modular Multilevel Converter model using PLECS are presented to validate the proposed control and topology performance. © 2022 IEEE.